Culture and collaboration - an underestimated power!? The effect of regional culture on the research collaboration propensity in European regions - Cathrin Söllner (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2021)
Collaboration is an important factor for regional economic growth. Still, the literature lacks explanations why some regions collaborate more or less than expected. The present paper proposes regional culture as influencing factor, being region-specific and connected to interactive activities. Estimations are based on a sample of 155,019 collaborative patents from 134 European NUTS-2 regions. Data on regional culture was extracted from the European Values Study. Results reveal that regional culture has a significant effect on the collaboration likelihood. This influence differs due to the various dimensions of regional culture.
Keywords: F00; O43; R11; 330; collaboration propensity; regional culture; Hofstede; EU-regions; patents